Effect of mismanagement towards abandoned project in Malaysia - Saidah An'nisaa, Salam; Nur Farhayu, Ariffin; N. F. N., Mohamad Noor; Mohammad Idris, Ali; N. I., Ramli (IOP Publishing, 2020)
Over the years, Malaysian government has placed significant emphasis on the need for citizens to have their own house. Unfortunately, the abandoned housing projects are indeed a major hiccup for purchasers who dreams to have their own home become reality. The abandonment of housing projects has resulted in many adverse consequences to the economy, society and environment. Therefore, this paper discuss on the effects of mismanagement in contribution to the abandoned housing project. Together, the suitable solutions to mitigate the abandonment issues will also be proposed. The studies focus on collecting the data form local authorities and also by doing a questionnaire. The data was analyse based on the Likert's scale and using relative of important index. This study found that the mismanagement is cause by the inexperienced developer with lack of management skill will contribute to the abandoned housing project.